SHMT1 siRNA-Loaded hyperosmotic nanochains for blood-brain/tumor barrier post-transmigration therapy. (February 2022) - Pandey, Shambhavi; Lee, Myung Chul; Lim, Jae woon; Choung, Yun-Hoon; Jang, Kyoung-Je; Park, Sang Bae; Kim, Jae Eun; Chung, Jong Hoon; Garg, Pankaj
Abstract: The near-perivascular accumulation in solid tumors and short-lived span in circulation, derails even the most competent nanoparticles (NPs) from achieving their maximum therapeutic potential. Moreover, delivering them across the blood brain/tumor barrier (BBB/BTB) is further challenging to sought anticancer effect. To address these key challenges, we designed a linearly aligned nucleic acid-complexed polydixylitol-based polymeric nanochains (X–NCs), with inherent hyperosmotic properties enabling transmigration of the BBB/BTB and navigation through deeper regions of the brain tumor. The high aspect ratio adds shape-dependent functional aspects to parent particles by providing effective payload increment and nuclear factor of activated T cells-5 (NFAT5)-mediated cellular uptake. Therefore, serine hydroxymethyltransferase 1 (SHMT1) siRNA-loaded nanochains not only demonstrated to transmigrate the BTB, but also resulted in remarkably reducing the tumor size to 97% in the glioblastoma xenograft brain tumor mouse models. Our study illustrates how the hyperosmotic nanochains with high aspect ratio and aligned structure can accelerate a therapeutic effect in aggressive brain tumors post-transmigration of the BBB/BTB by utilizing an NFAT5 mode of uptake mechanism.